Pendampingan Program Pemberian Makanan Tambahan (PMT) Pangan Lokal di Desa Tanjung dan Desa Kalijambe, Kecamatan Bringin, Kabupaten Semarang - Pontang, Galeh Septiar; Sri Setyaningsih; Anissa Putri Aliya; Zeinisa Fariza (UNIVERSITAS NGUDI WALUYO, 2025)
Pemberian Makanan Tambahan (PMT) Pangan Lokal program is a government initiative aimed at reducing the prevalence of stunting and wasting among children under five. PMT has the potential to increase nutrient intake where it is lacking in the diet. A study of the nutritional status of children under five in the villages of Desa Tanjung and Desa Kalijambe revealed that 6.3% exhibited stunting (impaired growth), and 74% demonstrated an energy deficit. A total of 13 children aged 12–59 months participated in the PMT programme, alongside YBM BRILiaN cadres and their mothers. The methodology encompasses observational studies, socialisation initiatives and training programmes for childcare providers and parents of young children. Direct intervention strategies were also employed during the 90-day intervention period. The intervention took the form of a comprehensive menu made available during the designated lunch period. Dietary intake data was collected using a 1x24-hour recall form, administered once every 30 days during the intervention period. It has been demonstrated that the mean energy and macronutrient intake of children under five has increased compared to the mean intake prior to the implementation of the providing supplementary food. A systematic and continuous monitoring process must be implemented within the programme to ensure the efficacy of PMT is preserved. ABSTRAK Program Pemberian Makanan Tambahan (PMT) pangan lokal merupakan salah satu upaya pemerintah untuk mencapai target penurunan balita stunting dan wasting. Program PMT berpotensi meningkatkan asupan zat gizi balita yang defisit. Di Desa Tanjung dan Desa Kalijambe terdapat 6,3% balita stunting dan 74% diantaranya balita memiliki asupan energi yang defisit. Pendampingan program PMT pangan lokal dilakukan pada 13 balita berusia 12-59 bulan dengan melibatkan peran kader dan ibu balita. Metode yang digunakan yaitu penyuluhan pada orang tua balita, pelatihan kepada kader serta intervensi program PMT pada balita selama 90 hari. Intervensi diberikan berupa paket menu lengkap saat jam makan siang. Pengambilan data asupan gizi menggunakan formulir recall 1x24 jam dilakukan tiap bulan selama intervensi. Hasil program diketahui bahwa rata-rata asupan energi dan zat gizi makro balita mengalami peningkatan dibandingkan sebelum PMT pangan lokal. Monitoring menu dalam program perlu dilakukan secara berkala dan terus menerus untuk mempertahankan daya terima PMT.